RANCANG BANGUN SISTEM PENGIDENTIFIKASI TRAVEL BAG PADA KELOMPOK BIRO PERJALANAN UMROH/HAJI BERBASIS WEB - Timbo Faritcan Parlaungan S.; Dede Wisnu (Jurnal Teknologi Informasi dan Komunikasi, 2020)
The development of Information Technology, one of which is engaged in Umrah Travel services. One of them is the process of recording and identifying the ownership of Umrah or Hajj participant bags. Recording done manually or on paper will make it difficult to identify the bag because it is at great risk for damage or loss.Web-based information systems that run on computer networks integrated with microcontroller hardware can be utilized for digital data recording and bag identification. The use of a system with a digital method will facilitate the identification of bags. Which will be faster and data stored securely.The design and manufacture of a web-based travel bag identification system using a microcontroller is a solution for the application of recording data and identification of participant bags from the Umrah or Hajj travel agency. By using this system the travel agency and participants will feel safe and comfortable because the risk of bag swapping is minimal. In addition, all bag and owner data is stored digitally and can be accessed.